Pengaruh Rasio Profitabilitas terhadap Kontribusi Dana Zakat Bank Umum Syariah di Indonesia - Fathuddin Abdi (Indonesian Journal of Islamic Economics and Business, 2019)
This study aims to determine the effect of profitability ratios on company zakat expenditure in Islamic banking in Indonesia. This study uses a quantitative approach with multiple linear regression data analysis techniques and classical assumption tests. The sample of this study consisted of 9 Islamic commercial banks using secondary data on the financial statements of each bank from 2012- 2016. The results showed that simultaneously, return on assets and return on equity have a significant effect on zakat expenditure in Islamic Commercial Banks in Indonesia. However, partially, return on assets has a negative and significant effect on zakat expenditure at Islamic Commercial Banks in Indonesia, while Return on equity has a positive and significant effect on zakat expenditure at Islamic Commercial Banks in Indonesia.